Pengaruh Pengetahuan dan Persepsi Mahasiswa terhadap Implementasi Teknologi Blockchain dalam Praktik Akuntansi - Septiani; Rudy Kurniawan; Rafles Ginting (Economic Reviews Journal, 2024)
With the rapid development of technology, the latest innovations such as Blockchain Technology are becoming increasingly important in various fields, including accounting. The potential of this technology to fundamentally change the way transactions are conducted and recorded has caught the attention of the business world, with the potential promise of cutting global infrastructure costs by up to $100 billion annually. However, knowledge and understanding of this technology is still limited among accounting students, especially in Indonesia. Previous research focused more on developed countries or the technical and security aspects of blockchain, so there is a research gap that needs to be filled regarding accounting students' knowledge and perceptions of blockchain technology, especially in Indonesia. The importance of understanding and acceptance of this technology among accounting students is an important question in the context of their preparation for future professional practice.